Career Development Training for Interventional Pulmonary Fellows: Are They Ready for the Workforce?. Issue 3 (July 2020) - Shafiq, Majid; Akulian, Jason; Desai, Neeraj; French, Kim; Sachdeva, Ashutosh; Lamb, Carla; Shojaee, Samira; Argento, Angela C.; Lee, Hans J.
Abstract : Background: Interventional pulmonary (IP) fellows spend ≥6 years of postgraduate medical education before IP training. Given the high employment attrition rates of early medical professionals, we investigated the IP fellows' self-assessed readiness for employment and the role of an intense preemployment educational intervention on improving the same. Materials and Methods: Over 2 consecutive academic years, IP fellows nationally were invited to a mid-year career development symposium focusing on employment search strategy and early career development. Attendees were anonymously surveyed presymposium/postsymposium and 6 months later at graduation. Both quantitative and qualitative data were collected. Attendees' knowledge and skills were rated on a 5-point Likert scale. A control group of IP fellows that did not attend the symposium were also surveyed at graduation. Results: In total, 53 of 55 attendees (96% response rate) completed the presymposium survey and 50 of 55 (91%) completed the final survey at graduation. Overall, 16 of 18 (89%) nonattendees also completed the final survey at graduation. IP Fellows reported low baseline self-assessment scores on all question domains. Scores increased significantly postsymposium and were sustained at graduation ( P <0.05). At graduation, the average response score of symposium attendees was significantly higher than that of nonattendees ( P =0.04). Overall, 84% reported that the symposium helped them with their employment search. Conclusion: Advanced IP fellows were not well-equipped for a strategic employment search and early career development at the onset of their IP fellowship training. Participation in an intense educational intervention significantly improved fellows' self-assessment scores, an effect that was sustained at 6 months. Abstract : Supplemental Digital Content is available in the text.